Impact of global climate change on stream low flows: A case study of the great Miami river watershed, Ohio, USA - Shrestha, Sabin; Sharma, Suresh; Gupta, Rishabh; Bhattarai, Rabin (International Journal of Agricultural and Biological Engineering, 2019)
Climate change will profoundly affect hydrological processes at various temporal and spatial scales. This study is focused on assessing the alteration of water resources availability and low flows frequencies driven by changing climates in different time periods of the 21st century. This study evaluates the adaptability of prevailing Global Circulation Models (GCMs) on a particular watershed through streamflow regimes. This analysis was conducted in the Great Miami River Watershed, Ohio by analyzing historical and future simulated streamflow using 10 climate model outputs and the Soil and Water Assessment Tool (SWAT). The climate change scenarios, consisting of ten downscaled Coupled Model Intercomparision Project Phase 5 (CMIP5) climate models in combination with two Representative Concentration Pathways (RCP 4.5 and RCP 8.5) were selected based on the correlation between observed records and model outputs. Streamflow for three future periods, 2016-2043, 2044-2071 and 2072-2099, were independently analyzed and compared with the baseline period (1988-2015). Results from the average of ten models projected that 7-day low flows in the watershed would increase by 19% in the 21st century under both RCPs. This trend was also consistent for both hydrological (7Q10, 1Q10) and biological low flow statistics (4B3, 1B3). Similarly, average annual flow and monthly flows would also increase in future periods, especially in the summer. The flows simulated by SWAT in response to the majority of climate model projections showed a consistent increase in low flow patterns. However, the flow estimates using the Max-Planck-Institute Earth System Model (MPI-ESM-LR) climate output resulted in the biological based low flows (4B3, 1B3) decreasing by 22.5% and 33.4% under RCP 4.5 and 56.9% and 63.7% under RCP 8.5, respectively, in the future when compared to the baseline period. Regardless, the low flow ensemble from the 10 climate models for the 21st century seemed to be slightly higher than that of historical low flows. Keywords: climate change, low flows, SWAT, climate models, Great Miami River Watershed DOI: 10.25165/j.ijabe.20191201.4486 Citation: Shrestha S, Sharma S, Gupta R, Bhattarai R. Impact of global climate change on stream low flows: A case study of the great Miami river watershed, Ohio, USA. Int J Agric & Biol Eng, 2019; 12(1): 84–95.